2009
DOI: 10.1089/jop.2009.0009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Eye Drops Inhibit the Early-Phase Reaction in a Type-I Allergic Conjunctivitis Model in Mice

Abstract: Those results suggest that administration of cyclosporine A eye drops inhibit the early-phase reaction in type-I allergic conjunctivitis, which may be mediated by the suppression of mast cell degranulation. This action of cyclosporine A eye drops may be involved in the therapeutic effect of cyclosporine A on allergic conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This was consistent with our report that showed that the instillation of CyA eye drops 1 h before antigen challenge did not inhibit an early phase reaction in a murine allergic conjunctivitis model. 18) We also reported that instillation of CyA eye drops at 1, 4 and 7 h after antigen-challenge inhibited eosinophil infiltration into conjunctiva in a murine allergic conjunctivitis model. 19) Therefore, it is suggested that the effects of CyA on the late phase reaction are not mediated by suppressing the early phase reaction.…”
Section: Discussionmentioning
confidence: 69%
“…This was consistent with our report that showed that the instillation of CyA eye drops 1 h before antigen challenge did not inhibit an early phase reaction in a murine allergic conjunctivitis model. 18) We also reported that instillation of CyA eye drops at 1, 4 and 7 h after antigen-challenge inhibited eosinophil infiltration into conjunctiva in a murine allergic conjunctivitis model. 19) Therefore, it is suggested that the effects of CyA on the late phase reaction are not mediated by suppressing the early phase reaction.…”
Section: Discussionmentioning
confidence: 69%
“…One study showed that applying a solution of ovalbumin onto the ocular surface elicited hind-paw scratching in sensitized BALB/c mice, whereas application of a ragweed pollen suspension did not. 93) We found that a subconjunctival injection of an extract of ragweed pollen elicited hind-paw scratching in ICR mice that had been immunized with ragweed pollen in combination with an aluminum hydroxide adjuvant, but not in mice immunized with ragweed pollen alone. 94) In contrast to mosquito bite allergy, pollen allergy-induced scratching was almost completely abolished by mast-cell deficiency.…”
Section: Pollen Allergymentioning
confidence: 80%
“…The results indicated no significant differences in ocular responses between the treatment and control groups (Figure D). No scratching behavior was observed in mice, and histological examinations with H&E staining showed no abnormalities (Figure E). These findings suggested that Th20 possessed good biocompatibility in the ocular region, supporting its potential for further research in drug delivery applications.…”
Section: Resultsmentioning
confidence: 96%